2017
DOI: 10.1136/openhrt-2017-000627
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different imaging modalities for successful percutaneous left atrial appendage closure

Abstract: ObjectivesAccurate sizing of the left atrial appendage (LAA) is essential when performing percutaneous LAA closure. This study aimed to compare different LAA imaging modalities and sizing methods in order to obtain successful LAA closure.BackgroundPercutaneous LAA closure is an increasingly used treatment strategy to prevent stroke in patients with atrial fibrillation. LAA sizing has typically been done by 2D-transoesophageal echocardiography (TEE).MethodsPatients who had a preprocedural TEE and preprocedural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…Our findings are consistent with previous comparisons of CT angiography to TEE for measuring LAA size, and provide further evidence that TEE has limitations in providing accurate size measurements . For the most part, TEE does allow acceptable sizing in terms of LAA ostial diameter and depth for successful completion of LAA occlusion.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are consistent with previous comparisons of CT angiography to TEE for measuring LAA size, and provide further evidence that TEE has limitations in providing accurate size measurements . For the most part, TEE does allow acceptable sizing in terms of LAA ostial diameter and depth for successful completion of LAA occlusion.…”
Section: Discussionsupporting
confidence: 89%
“…Transesophageal echocardiography (TEE) is currently employed as the standard for procedural measurement of the LAA ostial diameter and depth in the two‐dimensional (2D) omniplane views of 0°, 45°, 90°, and 135°. Studies comparing TEE sizing of the LAA with computed tomography (CT) imaging have shown more accurate LAA ostial diameter and depth with CT compared to TEE . However, routine use of CT is not commonly performed commercially due to lack of formal vendor recommendation, and is not feasible for every case at every institution due to workflow, cost, reimbursement, and the need for intravenous contrast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important possible complications are those associated with right heart catheterization such as pulmonary embolism, pericardial tamponade, but also bleeding from the puncture site, and vascular complications. Moreover, the mono-plane images may limit the usefulness of ICE in left atrial appendage occluder sizing [4].…”
Section: Discussionmentioning
confidence: 99%
“…Also TOE remains the gold standard for exclusion of thromboembolic material within the left atrium and in its appendage [2,3]. Nevertheless, some authors emphasize the advantages of computed tomography or cardiac magnetic resonance for exploration of the anatomy of the left atrial appendage and for the precise measurement of its dimensions [4,5]. Thus the debate on the optimal imaging strategy for the pre-procedural visualization of the left atrium is still open.…”
Section: Introductionmentioning
confidence: 99%